The causes of psychic indisposition is described unconsciously or discretely in 7x4-field form in famous works of art - Heiska, Juhani (IJRDO - Journal of Social Science and Humanities Research, 2017)
The 7x4-field is a tool for analysing and describing reasons for mental disorders, illnesses, abnormalities and malaise, as well as human distress in general. It has been developed on the basis of practical mental health work and numerous interviews, as well as for example using a factor analysis. It is also suitable for dealing with various processes of distress and mental wellbeing. It provides a broader view of these processes than can be achieved with certain kinds of still images. This article examines the observation that many famous works of arts describe, the same elements that are presented in 7x4-field’s different squares and how to make use of the result in education, culture study as well as other studies.